Marketing Strategy of Processed Catfish (Pangasius sutchi) Products in Koto Mesjid Village XIII Koto Kampar District Riau Province - Hasnibar, Sesni; Hamid, Hamdi; Bathara, Lamun (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in June-July 2014 on Koto Masjid Village and marketing spots of catfish processed product. This research aims to determine the marketing condition and the effective marketing strategies to support catfish processed bussines. The method used was a case study with respondent taking by sensus as many as 6 people catfish processors and by purposive sampling as many as 8 people from marketing participant population.Marketing strategy of catfish product are indentified into three main strategies: 1) market segmentation based on geographic factors include internal and externalsegments in Riau Province, 2) targeting, includes all segments of market (Full Market Coverage), and 3) Positioning, is where a supplier trying to meet the demand for the product catfish on each segment and figure the image to consumer, that the Kto Masjid Catfish Product has good taste made by fresh catfish. Based on the SWOT analysis, there are three strategies that can be implemented based on rating, such as 1) ST1: improving quality and price of the products processed catfish to avoid competition among processors, 2) WT2: the presence of institutions such as cooperative marketing to accomodate catfish processed, and 3) WO2: pursuing the procurement of modern fish processing tools to improve product quality catfish.Keywords: marketing strategies, catfish processed product, Koto Masjid Village